Analisis Perbandingan Kadar Nikel Hasil Pengeboran dengan Hasil Penambangan pada PT Ghanesa Wana Utama - Aldiyansyah; Husain, Jamal Rauf (Jurnal of Mining Insight, 2024)
The process of mining nickel resources at PT Gahnesa Wana Utama has problems in the form of differences in nickel content between the drill data and mining results data. Therefore, this study aims to determine the proportion of nickel grade values from drilling to mining results and to determine the factors that cause changes in nickel content values from drilling and mining results. The research method is carried out by analyzing the results of drill data with mining results. The results of the study showed that the drilling results obtained an average grade value of 1.64%, while mining results obtained an average grade value of 1.42%. This study shows that there has been a comparison of the difference in Ni content based on the results of drilling and mining results, namely 0.22%. The causative factors of changes in nickel levels are stagnant water in the stockpile, use of used sacks for samples, dredging of stockpile floors that are less clean, operators who are less attractive in ore collection, sampling errors and preparation errors.